Vulnerability, Ecclesial Abuse, and Vulnerable Adults - Carolina Montero Orphanopoulos (Journal of Moral Theology, 2023)
The term vulnerable adult has been used for decades within health or legal scientific reports describing potential subjects of abuse. More recently, it appears in relation to ecclesial abuse, as well as in psychologic and legal discussions in relation to the definition of these adults, and the reparation that they are owed. Admitting that the recognition of adult victims of abuse in the Catholic church is a breakthrough toward acknowledging the damage committed, the author states that the use of vulnerable adults to describe these victims is ambiguous. By redefining the ethical-anthropological category of vulnerability as an inherent human characteristic with a dual conception –anthropological and situational–she claims all people can be in either of these moments of experienced vulnerability, thus the inappropriateness of the term used to describe victims of ecclesial abuse.